The Effect COVID-19 On Earnings Quality and the Role of Corporate Governance as a Moderation - Febi Aji Riansyah; Pratana Puspa Midiastuty; Eddy Suranta (Yayasan Ilomata, 2023)
The aim of this research is to provide empirical evidence regarding the effect of Covid-19 on earnings quality with corporate governance as a moderator. Based on agency theory, corporate governance is a monitoring mechanism to improve quality. All manufacturing companies listed on the Indonesia Stock Exchange (BEI) with a research period of 2017-2022 were used as samples for this research. Using purposive sampling technique, the total of observations was 624 from 104 samples. Covid-19 is a dummy variable with the value (1) being in the Covid-19 period (2020-2022) and (0) other than the Covid-19 period (2017-2019). Corporate governance used in this research is the size of the board of directors and the proportion of independent commissioners. All hypothesis tested by using multiple linear regression techniques, IBM SPSS 25. Earnings quality is proxied by accrual earnings management and real earnings management. The research results prove that real earnings management occurs in the form of RM1, RM3 and RM TOTAL. Covid-19 does not cause the practice of accrual earnings management and real earnings management in the form of RM2. Furthermore, corporate governance is unable to moderate in explaining the relationship between Covid-19 and earnings quality.